Інституційне забезпечення фінансового механізму водокористування: теорія та практика - Тітаренко, Г.Б.; Тітаренко, О.В. (Економіка природокористування і сталий розвиток, 2020)
Обґрунтовано необхідність позитивних інституційних змін фінансового механізму водогосподарювання. Розглянуто основні інститути фінансування в системі водогосподарського комплексу України. Доведено необхідність формування інститутів розвитку, а саме: власності, управління, фінансового посередництва, позикового капіталу, ренти природних ресурсів, підприємництва. В системі фінансового механізму головну роль відведено інституту банківського кредитування. Визначено основні проблеми його функціонування та шляхи їх розв’язання. The statutes have the necessary positive and institutional benefits in the financial mechanism of water supply. The basic institute of financial security in the system of the water management complex of Ukraine is highlighted. The expediency of considering the institutional nature of financial support for the water management complex as a basis for optimization of economic systems has been proved. At the same time, it was noted that the market transformation of the Ukrainian Agrarian Union began without proper institutional support for the financial mechanism of the water management complex, which remained unchanged from the Soviet economic system, which does not meet the requirements of a market economy and needs a new revision. It is noted that the paradigm of institutionalism also provides an opportunity to determine the scenarios of financial support for the modernization of Ukraine. The necessity of formation of development institutes has been proved, among which in the research area are identified: institutes of property, management, financial intermediation, loan capital, rent of natural resources, entrepreneurship. It is determined that the development institute is an organizational and economic structure that facilitates the allocation of resources in favor of projects to realize the potential of economic growth. In the system of financial mechanism the main role is assigned to the Institute of Bank Lending. The basic problems of its functioning are revealed and the ways of their solution are determined. The main task of the National Bank of Ukraine is to expedite the problem of conducting currency swap operations, as they are able to solve the problem of shortage of national currency resources for the enterprises of Ukraine.